2022
DOI: 10.3390/atmos13050803
|View full text |Cite
|
Sign up to set email alerts
|

Co-Production System Based on Lean Methane and Biogas for Power Generation in Coal Mines

Abstract: The problem of low efficiency of coal mine methane utilization is caused by the concentration of methane of less than 10%, or a concentration that varies dramatically directly emitted into the atmosphere. This work deals with the concept of a co-production system that blends lean methane and biogas to produce electric energy. It is recommended to add the biogas generated by straws around the mines in a controlled manner to the lean methane flow to obtain the desired gas concentration in order to generate elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…For a single coal mine, the VAM flow rate can reach 1,000,000 m 3 /h, where the methane concentration is 0.5 vol % on average, assuming that this fraction of methane is fully utilized, and the annual treated VAM can reach 8.76 billion m 3 . In general, the oxidation rate of methane in TFRR is 90%; therefore, the purified gas emission for 1 year is 4.38 million m 3 and the thermal production can reach 1.4 GJ.…”
Section: Heat Utilization Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…For a single coal mine, the VAM flow rate can reach 1,000,000 m 3 /h, where the methane concentration is 0.5 vol % on average, assuming that this fraction of methane is fully utilized, and the annual treated VAM can reach 8.76 billion m 3 . In general, the oxidation rate of methane in TFRR is 90%; therefore, the purified gas emission for 1 year is 4.38 million m 3 and the thermal production can reach 1.4 GJ.…”
Section: Heat Utilization Approachmentioning
confidence: 99%
“…Because CH 4 concentrations in ventilation air are frequently less than 1 vol %, there are significant barriers in the mining industry to burning ventilation air methane and recovering and utilizing oxidation heat . Methane is considered the second biggest contributor to climate change and air pollution as it has 28 times the global warming potential (GWP) of carbon dioxide over 100 years . On the other hand, it is also a high-quality, clean-burning, renewable energy source that has been frequently employed in the energy industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also studies [3,30], aimed at improving the efficiency of using CMM with an efficiency close to 95 % when using gas piston units operating on a cogeneration or trigeneration cycle. The publication [31] considers the idea of joint use of CMM and biogas. It is shown that in this case the payback period will be about two years.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, one of the main CH 4 emission sources is coal mining, from which a large amount of low‐concentration (<1 %) CH 4 is emitted as ventilation air [5,6] . For a long time, ventilation‐air methane (VAM) not only causes waste of CH 4 resource, but also seriously affects the global environment [7] …”
Section: Introductionmentioning
confidence: 99%